SISTEM INFORMASI PEMAKAIAN ALAT-ALAT BERAT PADA DINAS BINA MARGA - Rahmadani (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2021)
The purpose of this study is to identify and design an Information System for the Use of Heavy Equipment at the Department of Highways with the programming languages HTML, PHP, CSS, JSON, AJAX and MySQL as database support. Broadly speaking, this research is divided into three stages, namely pre-development data collection, development and implementation, and post-development data collection. While in software development using the DSRM (Design Science Research Method). From the results of the study, it can be concluded that the information system on the use of heavy equipment at the Aceh Bina Marga Office has followed the procedure using HTML, PHP, CSS, JSON, AJAX and MySQL programming languages as database support.